The Functionalities of Online Ordering Book System - Zainab, Othman (2004)

(untitled)
The purpose of this project is to identify the functionality of Online Ordering Book System using object oriented concept based in Cooperative Universiti Technologi MARA, Pahang branch (UiTM) also to validate the identified functionality using horizontal prototype development technique by the user testing. Through the horizontal prototype, it serves as a guide for system developers to develop the real system based on the user requirements which will save time and decrease effort in the system development process, save cost and increase the quality of the developed system. Problems on the use of ordering book system and computer application were identified. An Online Ordering Book System was designed based on the requirement of Co-operative UiTM Pahang and lecturers. The methodology for this project is derived from the requirements analysis phases which comprise three main phases that are define requirements, analyze requirements ad validate the functionality of online ordering book system using the horizontal prototype. Unified Modeling Language (UML) notation was adopted for the development of horizontal prototype. This project involved the use case diagram, use case specification, class diagram, sequence diagram, collaboration diagram, activity diagram and the list of requirements. This design was used the PHP language in order to show the interface of this system.